Prove the identity: (cos x + cos y)^2 + (sin x – sin y)^2 = 2 + 2cos(x + y)

Expert Answers

An illustration of the letter 'A' in a speech bubbles

 

The identity `(cos x + cos y)^2 + (sin x – sin y)^2 = 2 + 2cos(x + y)` has to be proved.

Start from the left hand side.

`(cos x + cos y)^2 + (sin x – sin y)^2`

=> `cos^2 x` + `cos^2 y` + `2*cos x*cos y` + `sin^2 x` + `sin^2 y` - `2*sin x*sin y`

=> `cos^2 x + sin^2 x` + `cos^2 y + sin^2 y` + `2*cos x*cos y - 2*sin x*sin y`

=> `1 + 1 + 2*(cos x*cos y - sin x*sin y)`

Use the relation `cos(x + y) = cos(x)cos(y) - sin(x)sin(y)`

=> 2 + 2*cos (x + y)

This proves that (cos x + cos y)^2 + (sin x – sin y)^2 = 2 + 2cos(x + y)

 

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial